Implementasi Kolaborasi Internasional di Bidang Informasi dan Perpustakaan - Suyono, Hanny Chairany; Ridwan, Muhammad (Perpustakaan Universitas Gadjah Mada, 2023)
Libraries as one of the institutions that manage and disseminate information, are required to present information that is easily accessible anytime and anywhere needed by users. Based on this, the library needs to collaborate in order to maximize efforts in fulfilling information needs to users. The purpose of this paper is to find out how international collaboration is implemented in libraries. Collaboration can improve the quality of management and services in the library so that all activities in the library become more effective and efficient. Collaboration can be done nationally or internationally. Internationally there are several organizations that accommodate in the field of library and information science including IFLA, COCI, and CONSAL. The realization of international library collaboration is found in academic libraries, namely American Corner, French Corner, Indian Corner, Japan Corner, Australian Corner, and so on. In addition, an example of a university library that collaborates globally is the Libraries of Leiden University. Libraries of Leiden University is an academic library based in the city of Leiden, the Netherlands. Libraries of Leiden University has many branch libraries in other countries including one of them in Indonesia, precisely in Jakarta, namely KITLV-Jakarta